Pengaruh Sebaran Konsentrasi Klorofil-a Berdasarkan Citra Satelit terhadap Hasil Tangkapan Ikan Tongkol (Euthynnus sp) Di Perairan Selat Bali - Prayoga, I Made Satya; Putra, I Dewa Nyoman Nurweda; Dirgayusa, I Gusti Ngurah Putra (Journal of Marine and Aquatic Sciences, 2017)
One of fisheries potential in Bali Strait is tuna fish ( Euthynnus sp ). Tuna fish ( Euthynnus sp ) resources is highly influenced by waters productivity which indicated by the chlorophyll-a concentration distribution. The aims of this study are: to find out the concentration spatial of chlorophyll-a distribution in Bali strait, to find out temporal variability of chlorophyll-a and tuna fish ( Euthynnus sp ) in Bali strait, and to find out the influence of chlorophyll-a concentration distribution to the catch of tuna fish ( Euthynnus sp ) in Bali strait. The analysis of the influence of chlorophyll-a concentration distribution to the catch of tuna fish ( Euthynnus sp ) in Bali strait uses regression polynomial order 2, correlation, and cross correlation. The influence of chlorophyll-a concentration distribution to the catch of tuna fish ( Euthynnus sp ) in Bali strait yearly time series climatology amounted to R 2 = 0,1624 or 16,24%, the correlation coefficient values obtained by r = 0,1889. Seasonal time series climatology in west season (December - February) R 2 = 0,0707 or 7,07%, the correlation coefficient values obtained by r = 0,0749. The transitional season 1 (March - May) R 2 = 0,0095 or 0,95%, the correlation coefficient values obtained by r = - 0,0092. The east season (June - August) R 2 = 0,086 or 8,6%, the correlation coefficient values obtained by r = - 0,2155. The transitional season 2 (September - November) R 2 = 0,0482 or 4,82%. The correlation coefficient values obtained by r = - 0,1805